Topography Of Short Hepatic Veins And Interface Veins For Safe Tunneling During Hanging Maneuver Of Liver (Journal of Society of Surgeons of Nepal, 2023)
Introduction: During hanging maneuver liver resection, a tunnel is created at the interface of the liver and Inferior venacava (IVC). Gap between the middle and right hepatic vein is known as Fossa venacava. A gap between the Inferior right hepatic vein and the Caudate vein is known as a Vein gap. The Fossa venacava and Vein gap provide a safe plane for the insertion of forceps during tunneling. The aim of this study is to determine the topography of this safe plane.Methods: A cross-sectional study was done. Twenty livers were used in our study. Major hepatic veins, distance of Vein gap, Fossa venacava, and each vessel present at the interface between liver and IVC was measured by a Vernier caliper. All the collected data was entered and analyzed by using Statistical Package for Social Sciences version 20 (SPSS-20). Results: The average length of retro hepatic IVC was 49.5±10.5 mm and the diameter of 25.6±4.4 mm. The inferior right hepatic vein was present in 60% of cases while the Caudate vein was present in 85% of cases. Fossa venacava had an average distance of 12.3±3.46 mm and the Vein gap was 18.9±7.1 mm.Conclusion: While tunneling between IVC and the liver, Fossa venacava could be as small as 4.6 mm. The shortest distance of the Vein gap could be as small as 5.8 mm. The intermediate course of forceps insertion is safer than the right or left course.